3D multislice CT angiography in post-aortic stent grafting: A pictorial essay - Sun, Zhonghua (Korean Radiological Society, 2006)
Helical CT angiography has been widely used in both pre-and post-aortic stent grafting and has been confirmed to be the preferred modality when compared to conventional angiography. Recent development of multislice CT (MSCT) has further enhanced the applications of CT angiography in aortic stent grafting. One of the advantages of MSCT angiography over conventional angiography is that 3D reconstructions based on volumetric CT data provide additional information in the follow-up of aortic stent graft. While endovascular repair has been increasingly used in clinical practice, 3D MSCT imaging in endovascular repair continues to play an important role. In this pictorial essay, we aimed to discuss the diagnostic performance of 3D MSCT angiography in post aortic stent grafting, including the most commonly used surface shaded display, curvilinear reformation, maximum intensity projection, volume rendering and virtual endoscopy. Advantages and disadvantages of each 3D reconstruction were also explored.